Constraint-induced movement therapy enhances angiogenesis and neurogenesis after cerebral ischemia/reperfusion - Zhai, Zhi-Yong (Neural Regen Res, 2019)
Constraint-induced movement therapy after cerebral ischemia stimulates axonal growth by decreasing expression levels of Nogo-A, RhoA, and Rho-associated kinase (ROCK) in the ischemic boundary zone. However, it remains unclear if there are any associations between the Nogo-A/RhoA/ROCK pathway and angiogenesis in adult rat brains in pathological processes such as ischemic stroke. In addition, it has not yet been reported whether constraint-induced movement therapy can promote angiogenesis in stroke in adult rats by overcoming Nogo-A/RhoA/ROCK signaling. Here, a stroke model was established by middle cerebral artery occlusion and reperfusion. Seven days after stroke, the following treatments were initiated and continued for 3 weeks: forced limb use in constraint-induced movement therapy rats (constraint-induced movement therapy group), intraperitoneal infusion of fasudil (a ROCK inhibitor) in fasudil rats (fasudil group), or lateral ventricular injection of NEP1–40 (a specific antagonist of the Nogo-66 receptor) in NEP1–40 rats (NEP1–40 group). Immunohistochemistry and western blot assay results showed that, at 2 weeks after middle cerebral artery occlusion, expression levels of RhoA and ROCK were lower in the ischemic boundary zone in rats treated with NEP1–40 compared with rats treated with ischemia/reperfusion or constraint-induced movement therapy alone. However, at 4 weeks after middle cerebral artery occlusion, expression levels of RhoA and ROCK in the ischemic boundary zone were markedly decreased in the NEP1–40 and constraint-induced movement therapy groups, but there was no difference between these two groups. Compared with the ischemia/reperfusion group, modified neurological severity scores and foot fault scores were lower and time taken to locate the platform was shorter in the constraint-induced movement therapy and fasudil groups at 4 weeks after middle cerebral artery occlusion, especially in the constraint-induced movement therapy group. Immunofluorescent staining demonstrated that fasudil promoted an immune response of nerve-regeneration-related markers (BrdU in combination with CD31 (platelet endothelial cell adhesion molecule), Nestin, doublecortin, NeuN, and glial fibrillary acidic protein) in the subventricular zone and ischemic boundary zone ipsilateral to the infarct. After 3 weeks of constraint-induced movement therapy, the number of regenerated nerve cells was noticeably increased, and was accompanied by an increased immune response of tight junctions (claudin-5), a pericyte marker (α-smooth muscle actin), and vascular endothelial growth factor receptor 2. Taken together, the results demonstrate that, compared with fasudil, constraint-induced movement therapy led to stronger angiogenesis and nerve regeneration ability and better nerve functional recovery at 4 weeks after cerebral ischemia/reperfusion. In addition, constraint-induced movement therapy has the same degree of inhibition of RhoA and ROCK as NEP1–40. Therefore, constraint-induced movement therapy promotes angiogenesis and neurogenesis after cerebral ischemia/reperfusion injury, at least in part by overcoming the Nogo-A/RhoA/ROCK signaling pathway. All protocols were approved by the Institutional Animal Care and Use Committee of China Medical University, China on December 9, 2015 (approval No. 2015PS326K).